Strategies to Increase Drug Penetration in Solid Tumors - Choi, Il-Kyu; Strauss, Robert; Richter, Maximilian; Yun, Chae-Ok; Lieber, Andre (Frontiers in Oncology, 2013)
Despite significant improvement in modalities for treatment of cancer that led to a longer survival period, the death rate of patients with solid tumors has not changed during the last decades. Emerging studies have identified several physical barriers that limit the therapeutic efficacy of cancer therapeutic agents such as monoclonal antibodies, chemotherapeutic agents, antitumor immune cells, and gene therapeutics. Most solid tumors are of epithelial origin and, although malignant cells are de-differentiated, they maintain intercellular junctions, a key feature of epithelial cells, both in the primary tumor as well as in metastatic lesions. Furthermore, nests of malignant epithelial tumor cells are shielded by layers of extracellular matrix (ECM) proteins (e.g. collagen, elastin, fibronectin, laminin) whereby tumor vasculature rarely penetrates into the tumor nests. In this chapter, we will review potential strategies to modulate the ECM and epithelial junctions to enhance the intratumoral diffusion and/or to remove physical masking of target receptors on malignant cells. We will focus on peptides that bind to the junction protein desmoglein 2 (DSG2) and trigger intracellular signaling, resulting in the transient opening of intercellular junctions. Intravenous injection of these junction openers increased the efficacy and safety of therapies with monoclonal antibodies, chemotherapeutics, and T-cells in mouse tumor models and was safe in non-human primates. Furthermore, we will summarize approaches to transiently degrade ECM proteins or downregulate their expression. Among these approaches is the intratumoral expression of relaxin or decorin after adenovirus (Ad)- or stem cell-mediated gene transfer. We will provide examples that relaxin- based approaches increase the antitumor efficacy of oncolytic viruses, monoclonal antibodies, and T-cells.